2017
DOI: 10.1111/ans.14126
|View full text |Cite
|
Sign up to set email alerts
|

Semi‐Automatic Electronic Stent Register: a novel approach to preventing ureteric stents lost to follow up

Abstract: The SAESR allowed us to improve upon our better than expected rate of stents lost to follow up or severely delayed. We demonstrated non-inferiority in the rate of lost or severely delayed stents, and a number of other advantages including savings in personnel costs. The semi-automatic register represents an effective way of reducing the risk associated with a common urological procedure. We believe that this methodology could be implemented elsewhere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A total of 4,581 stents placed in 9 different studies were included in our final analysis (see table). 7–15 Overall, lost or retained stent rates ranged from 1.2% to 13% and were reduced to <1% with the use of tracking systems in most of the studies. Additionally, detection of lost stents was maintained over time.…”
Section: Resultsmentioning
confidence: 98%
“…A total of 4,581 stents placed in 9 different studies were included in our final analysis (see table). 7–15 Overall, lost or retained stent rates ranged from 1.2% to 13% and were reduced to <1% with the use of tracking systems in most of the studies. Additionally, detection of lost stents was maintained over time.…”
Section: Resultsmentioning
confidence: 98%
“…One study of the use of computerized tracking reported a missed stent rate of 1.2% (19). Rates of 1.2% with the billing record system and 0.5% with smartphone apps have been reported (20,21). We think that, no matter what measures are taken, the problem of missed stents cannot be eradicated so long as the human factor (patient or doctor) remains, and that new types of ureteral stents capable of self-absorption need to be developed in order to protect against missed stents.…”
Section: Discussionmentioning
confidence: 99%